'Give Me Some Rail': An Enquiry into Puzzle of Declining Female Labour Force Participation Rate. (February 2021) - Gupta, Rajesh; Bhamoriya, Vaibhav
Female labour force undeniably constitutes half of the human capital that drives the growth and development of emerging economies. Probing into determinants of female labour force participation decline has gathered momentum in recent past, but there has been no significant breakthrough in resolving the puzzle. Using World Bank's database of female labour force participation rate of India and China, and the state-wise database for India, this article juxtaposes the intermodal transport trend to examine if the former can be explained by the latter. Decline of female labour force participation in India is a concern from both the demographic dividend aspect and the social inclusion aspect. Twenty-five years' data of both China and India and 3 year's data of 18 Indian states show this trend, and this article probes the mobility constraint as the reason behind this phenomenon. Results of this study indicate that lower rail-to-road ratio is exclusionary for women. The findings regarding gendering of mobility and employment would influence important policy towards planning intermodal transport and its share of total transport for a nation. JEL Classification: C25, J12, J16, J21, J22, J130, J220, I38, I180, R48